2012
DOI: 10.1152/ajpheart.00439.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impaired blood pressure recovery to hemorrhage in obese Zucker rats with orthopedic trauma

Abstract: We have shown that obese Zucker rats with orthopedic trauma (OZT) exhibit a loss of arteriolar tone in skeletal muscle. We hypothesize that the loss of arteriolar tone in OZT blunts vasoconstrictor responses to hemorrhage, resulting in an impaired blood pressure recovery. Orthopedic trauma was induced with soft tissue injury and local injection of bone components in both hindlimbs in lean (LZT) and OZT (11–13 wk). One day after the orthopedic trauma, blood pressure responses following hemorrhage were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Frisbee et al showed that unconscious obese Zucker rats (OZ) exhibited significantly impaired blood pressure recovery after losing 10% of volume in 4 successive increments (Frisbee 2006). However, in our previous study, conscious OZ with a 20% loss of volume and an additional 10% loss after a 40-minute recovery did not exhibit impaired blood pressure compensation as compared to lean Zucker rats (LZ) (Xiang et al 2012). This inconsistency raises the possibility that anesthesia interferes with the blood pressure regulation following hemorrhage differently between lean and obese rats.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Frisbee et al showed that unconscious obese Zucker rats (OZ) exhibited significantly impaired blood pressure recovery after losing 10% of volume in 4 successive increments (Frisbee 2006). However, in our previous study, conscious OZ with a 20% loss of volume and an additional 10% loss after a 40-minute recovery did not exhibit impaired blood pressure compensation as compared to lean Zucker rats (LZ) (Xiang et al 2012). This inconsistency raises the possibility that anesthesia interferes with the blood pressure regulation following hemorrhage differently between lean and obese rats.…”
Section: Introductionmentioning
confidence: 76%
“…It is proposed that reduction in ventricular filling pressure after severe hemorrhage increases cardiac vagal outflow via myocardial mechanoreceptors (Bezold-Jarish reflex), resulting in decreased heart rate (Campagna and Carter 2003; Mark 1983). This parasympathetic nerve-mediated bradycardia following severe hemorrhage appears to be elevated in OZ and diabetic rats (Boku et al 2010; Xiang et al 2012). Although the mechanisms and significance of this post-hemorrhagic bradycardia are unclear, the similar cardiac output between LZ and OZ after hemorrhage suggests that a blunted increase in TPR rather than bradycardic hypotension is responsible for the impaired blood pressure compensation in OZ.…”
Section: Discussionmentioning
confidence: 98%
“…by 2.5% of ethanol solution. We have previously shown that this ethanol concentration in the superfusion is approximately 1/1,000 and does not have any effects on vascular reactivity .…”
Section: Methodsmentioning
confidence: 92%
“…glibenclamide administration (10 mg/kg; 30 minutes prior exercise). We have shown that this treatment method inhibits K ATP activation [29].…”
Section: Ogtt and Blood Pressure Measurementsmentioning
confidence: 88%
“…We produced several podcasts in the field of vascular biology and microcirculation (7, 8, 10, 23,33,34,39,41,53,57,58,67,76,105,106,115,116), and we wish to highlight several key podcasts here. We discussed a human study that looked at the central blood pressure response to the cyclooxygenase inhibitor indomethacin in both old and young healthy adults (5), which addressed the question: What happens when you combine nonsteroidal anti-inflammatory drug-type pain medication and aging-induced arterial stiffening?…”
Section: Podcastsmentioning
confidence: 99%